Problem osoby / Philippe Cormier ; tł. Mirosław Mejzner i Lucjan Balter. - Cormier, Philippe (1948- )
1. Przedtem. 2. Chrystus. 3. Unia hipostatyczna. 4. Trójca. 5. Osoba ludzka. 6. Powrót do unii hipostatycznej.